Mapping of budget stress in Indonesia: Consequence on budget implementation - Tehupuring, Ronald (Badan Pemeriksa Keuangan Republik Indonesia, 2021)
The phenomenon of a budget deficit in local governments at the provincial, regency, and city levels shows that there is budget stress. Budget stress is a regional fiscal condition reflected in the lower revenue budget, while regional expenditure is getting higher. The consequence of budget stress is low budget implementation, and it reduces the quality of services to the public. This study aims to map the regions experiencing budget stress at the local government levels. Furthermore, this study examines and analyzes the consequences of budgetary stress on budget implementation. The research sample used local governments at the provincial, regency, city levels throughout Indonesia during 2016-2020. This study uses Ordinary Least Square (OLS) to test the research hypothesis. This study groups the five regions with the highest budget stress during 2016-2020. The results of this study can contribute to the theory, methodology, and implementation related to the budget. The theory's contribution is that the political budget cycle can maintain government performance through various efforts to reduce budget stress. This study also found that budget stress can reduce budget implementation. Therefore, the government needs to pay attention to indicators of budget stress.